Pendampimgan Pembelajaran Daring Bagi Siswa jenjang Madrasah Ibtidaiyah Selama Pandemi Covid-19 di Dusun Banaran Desa Tunglur Kecamatan Badas - Umi Salamatud Diniyah; Uzer Mustagfirin (LP3M IAIFA Kediri, 2021)
The learning process becomes a system in learning. The learning system consists of several components that interact with each other until effective interaction is obtained. But currently learning cannot be done face-to-face but online, because the Covid-19 virus is spreading to various countries in the world. The existence of the outbreak that makes a threat to the whole world certainly makes a global polemic. In the educational process, learning activities that were originally carried out face-to-face, were converted into distance learning. In online teaching and learning activities, there must be a lot of unwanted distractions. When studying through online students cannot freely ask questions such as studying face-to-face. Some parents do not understand technology. Therefore, researchers took the initiative to carry out an online learning assistance program for children so that they understood the material conveyed by the teacher's father / mother through the whatsapp group. In this study, researchers used the PAR (Participacory Action Research) method. The PAR method is one of the research models that look for something to connect the research process into the process of social change. By directly participating in accompanying children to online learning. With this program, it is hoped that it can help children's difficulties in online learning.